Respon Sawi pada Berbagai Konsentrasi dan Waktu Pemberian Ekstrak Air Kulit Buah Jengkol Segar - Simanjuntak, Putriany; Nurjanah, Uswatun; Turmudi, Edhi (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2016)
The aim of this study was to evaluate the response of mustard to various concentrations of jiringa-pericarp water extract applied before or at planting . The study was conducted in November 2015-January 2016 located in a greenhouse using Completely Randomized Design, 2 factors and 4 replications. The first factor, concentration of jiringa-pericarp water extract consisted of 6 treatments: 165 g / L, 330 g / L, 495 g / L, 660 g / L, 825 g / L and 990 g / L and as comparison were 4 control plants. The second factor consisted of application one week before planting and at the time of planting. Each experimental unit consisted of two plants. The results showed that the application jiringa extract at palnting time with the concentration of 825 g / L resulted in the lowest leaf area and root fresh weight. The percentage of mus tard growth inhibition respectively were 51.54% and 56.69% when compared to the control. Jiringa water extract applied at planting time inhibited mustard growth more significant when compared to that 1 week before planting. The lowest average values for variables of leaf number, fresh weight and crown dry weight were obtained at 825 g / L concentration with a percentage of obstacles of 35.57%; 47.16% and 40.70% when compared with controls.